A linguistic landscapes study in Indonesian sub-urban high school signages: an exploration of patterns and associations - Yustika Wahyu Riani; Ana Widia Ningsih; Mery Novitasari; Mochammad Sulthon Samudra Rizky Zulkarnaen (English, 2021)
English is the most used lingua franca and its permeation is mainly through education sector. This expansion is reflected through the display of English coexisting with other languages in education sites. Linguistic landscape study in school sites helps to explain the functions of language choices in school signs. In Indonesia, the use of English captured in school signs have been frequently investigated focusing in their relation with urban communities, yet, the co-existence of languages in signages in sub-urban schools are still rarely investigated. To fill this gap, we scrutinized the languages present on Indonesian sub-urban schools focusing on their patterns and associations. 101 school signs were collected from three senior high schools in sub-urban areas in Jember, Magetan and Situbondo. The display patterns were analyzed based on the number of languages present in the signs and interpreted socio-culturally. This study found three patterns of the suburban school signs: monolingual, bilingual, and multilingual signs consisting of five different languages: Indonesian, English, Arabic, Sanskrit, and Latin. Indonesian becomes the dominant language used, and is followed by English. English is mostly used in schools that have history as international schools. In addition, Arabic is mostly used in school located in Islamic environment as a form of self-identification, and Sanskrit is used as a cultural symbol in the school located in dominant Javanese community. In conclusion, location and socio-cultural context influence the language used in school.